From mine waste to engineered growth media: reflecting on how to reduce reliance on topsoil for rehabilitation in Western Australia - Salfate, E; Esmi, M; Robertson, L (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
The scarcity of topsoil poses a recurrent challenge for mine sites across Australia and beyond, where every cubic metre becomes a contested resource in the battle to achieve progressive closure and rehabilitation goals. The use of topsoil is generally driven by the need to quickly achieve vegetation growth and meet stringent rehabilitation targets. At the same time, natural soils are generally the go-to source for engineered fills and construction materials for final landforms. In the rush of meeting closure and rehabilitation outcomes, are we at risk of potentially wasting high-value, limited and non-renewable resources (topsoil) over areas that may have limited potential productivity? Are we mistakenly assuming that new borrow sites are required, when potentially suitable materials are already being produced by the mine? This paper is an invitation to reflect (once again) on the use of alternative strategies to engineer fill materials to construct final closure landforms and create growth media for vegetation, especially in areas where productive soils are already scarce, such as the Pilbara region in Western Australia. Laboratory testing results and field observations are combined to discuss and illustrate that some mine waste materials, such as non-toxic iron ore tailings and spoils, may be combined (or engineered) to resemble the physical properties of surrounding natural soils and initiate rehabilitation through vegetation establishment. The paper also expands on the need to remain mindful and aware of the opportunities provided by other non-mining waste streams as they may provide that ‘missing ingredient’ required to create an all-encompassing ‘engineered growth media’. This paper emphasises the necessity for stakeholder collaboration to progressively adopt the concept that wastes produced by mining and other industries can serve an alternative and productive purpose. It ultimately reflects on the change in mentality required to embrace the adoption of circular economy principles in mine waste management and rehabilitation practices, all with the ultimate objective of reducing the reliance on, and demand for, scarce natural resources such as natural soils.
Keywords: closure